2023
DOI: 10.3390/cells12121583
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling White Adipose Tissue Heterogeneity and Obesity by Adipose Stem/Stromal Cell Biology and 3D Culture Models

Abstract: The immune and endocrine dysfunctions of white adipose tissue are a hallmark of metabolic disorders such as obesity and type 2 diabetes. In humans, white adipose tissue comprises distinct depots broadly distributed under the skin (hypodermis) and as internal depots (visceral). Depot-specific ASCs could account for visceral and subcutaneous adipose tissue properties, by regulating adipogenesis and immunomodulation. More importantly, visceral and subcutaneous depots account for distinct contributions to obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 129 publications
0
3
0
Order By: Relevance
“…As adipose tissue is a highly heterogeneous organ, its depots are biologically different, which is reflected in differences in the expression profiles of various genes, and translates into differences in lipolytic and inflammatory activity or insulin sensitivity [2]. In obesity, the functional differences between the different adipose tissue depots might be both accentuated and abolished [19,22], and these processes can be mediated by epigenetic mechanisms that buffer the effects of the environment [23]. There are many potential reasons for the discrepancy between our findings and the Gaens et al study, such as differences in gender and metabolic status (in the study by Gaens et al, 30% of the participants were men and most of the patients had impaired glucose tolerance or T2DM) [21].…”
Section: Discussionmentioning
confidence: 99%
“…As adipose tissue is a highly heterogeneous organ, its depots are biologically different, which is reflected in differences in the expression profiles of various genes, and translates into differences in lipolytic and inflammatory activity or insulin sensitivity [2]. In obesity, the functional differences between the different adipose tissue depots might be both accentuated and abolished [19,22], and these processes can be mediated by epigenetic mechanisms that buffer the effects of the environment [23]. There are many potential reasons for the discrepancy between our findings and the Gaens et al study, such as differences in gender and metabolic status (in the study by Gaens et al, 30% of the participants were men and most of the patients had impaired glucose tolerance or T2DM) [21].…”
Section: Discussionmentioning
confidence: 99%
“…also found that V-ASCs and S-ASCs release inflammatory and angiogenesis cytokines differently. Moreover, ASCs in the superficial layer, located closer to the dermis, exhibited hyperplastic and angiogenic capacities, while ASCs in the deep layer were characterized by inflammatory properties similar to V-ASCs (27).…”
Section: Types Of Adipose Tissuementioning
confidence: 98%
“…These cells possess enhanced abilities to maintain their stemness and display multilineage plasticity compared to cells cultured in adhesion (26). Moreover, 3D cells more closely mirror biological processes compared to cells cultured in traditional monolayers, driving the need for the development of 3D culture, including spheroids, organoids, organ-on-a-chip models, and bioprinting (27)(28)(29).…”
mentioning
confidence: 99%